2023
DOI: 10.1001/jamanetworkopen.2023.41165
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and Safety of Dostarlimab Monotherapy in Patients With Mismatch Repair Deficient Solid Tumors

Thierry André,
Dominique Berton,
Giuseppe Curigliano
et al.

Abstract: ImportanceMismatch repair deficiency (dMMR) occurs in various cancers, and these tumors are attractive candidates for anti–programmed cell death 1 therapies, such as dostarlimab, a recently approved immune checkpoint inhibitor.ObjectiveTo assess the antitumor activity and safety of dostarlimab in patients with advanced or recurrent dMMR solid tumors.Design, Setting, And ParticipantsThe GARNET trial was a phase 1, open-label, single-group, multicenter study that began enrolling May 8, 2017. Participants had adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“… 1317 Dostarlimab (Jemperli) developed by GSK was approved in 2021 and used in patients with mismatch repair-deficient advanced solid tumors. 1318 …”
Section: Tumor Biomarker-based Cancer Therapymentioning
confidence: 99%
“… 1317 Dostarlimab (Jemperli) developed by GSK was approved in 2021 and used in patients with mismatch repair-deficient advanced solid tumors. 1318 …”
Section: Tumor Biomarker-based Cancer Therapymentioning
confidence: 99%
“…Another PD-1 monoclonal antibody, dostarlimab, was approved in 2021 and tested in clinical trials (NCT04165772) in patients with MSI-H or dMMR CRC[ 141 ]. A high-resolution structure revealed that Dostarlimab binds to the flexible loops of PD-1, including the BC, C’D, and FG loops, in contrast to the binding modes of Pembrolizumab or Nivolumab[ 94 ].…”
Section: Clinical Trials Involving Checkpoint Inhibitors In Crcmentioning
confidence: 99%
“…In the second- or third-line setting, there are multiple phase I/II clinical trials reporting on the efficacy of PD-L1/PD-1 inhibitors: pembrolizumab, dostarlimab, nivolumab, and avelumab, with similar results, with an ORR between 30–38% [ 86 , 96 , 105 , 106 ]. The phase II Checkmate 142 trial tested the PD-1 and CTLA4 dual blockade in pre-treated patients, reporting a ORR of 55%, mPFS not reached [ 107 ].…”
Section: Immune Checkpoint Inhibition In Crcmentioning
confidence: 99%